Crystal structure of tin(IV) chloride octahydrate - Hennings, Erik (Acta Crystallogr Sect E Struct Rep Online, 2014)
The title compound, [SnCl(4)(H(2)O)(2)]·6H(2)O, was crystallized according to the solid–liquid phase diagram at lower temperatures. It is built-up of SnCl(4)(H(2)O)(2) octahedral units (point group symmetry 2) and lattice water molecules. An intricate three-dimensional network of O—H⋯O and O—H⋯Cl hydrogen bonds between the complex molecules and the lattice water molecules is formed in the crystal structure.